The use of capillary electrophoresis with contactless conductivity detection for monitoring of glycerol in adipose tissues during a sporting performance - Tůma, Petr; Málková, Klára; Wedellová, Zuzana; Samcová, Eva; Stulík, Karel (Electrophoresis, 2010)
A CE procedure employing capacitively coupled contactless conductivity detection has been developed for direct determination of the glycerol and mannitol polyalcohols in biological and pharmacological samples. Both glycerol and mannitol are fully separated from the sample matrix within very short times of 3.0 and 3.9 min, respectively, when using the optimized BGE, 60 mM H3BO3+30 mM LiOH (pH 9.1). The LODs amount to 0.5 microM for glycerol and 0.3 microM for mannitol. The repeatability of the glycerol determination in real biological materials is characterized by the coefficient of variation values, 0.5 and 3.2%, for the migration time and the peak area, respectively. The procedure has been used to monitor the free glycerol concentration in adipose tissue microdialyzates. A physiological study has demonstrated that the lipolysis occurring during a sporting action can be stimulated by local application of adrenaline. The procedure has further been utilized to determine mannitol in a pharmacological preparation.
Keywords: Glycerol; lineární modely; Acetonitriles; sloučeniny lithia; elektrická vodivost; tuková tkáň; cvičení; glycerol; Calibration; Adipose Tissue; Lipolysis; senzitivita a specificita; Lithium Compounds; kyseliny borité; lidé; Sensitivity and Specificity; Boric Acids; Bicycling; Linear Models; mannitol; acetonitrily; Hydrogen-Ion Concentration; kalibrace; lipolýza; koncentrace vodíkových iontů; elektroforéza kapilární; Reproducibility of Results; cyklistika; reprodukovatelnost výsledků; Electrophoresis, Capillary; Electric Conductivity; Humans; Mannitol; Exercise